Pelarasan Gamelan Jawa - Risnandar Risnandar (Pascasarjana Institut Seni Indonesia Surakarta, 2018)
Penelitian gamelan tuning adalah merumuskan teknik penyetelan gamelan Jawa. Gamelan pelaras. Belum ada teori atau cara kerja penyetelan gamelan, harmonisator umumnya masih mengandalkan insting dan pengalaman. Hal ini mengakibatkan generasi berikutnya sulit untuk meniru generasi senior, dan ada kemungkinan ilmu laras gamelan terdistorsi karena kematian Umpu untuk menyelaraskan gamelan. Penelitian ini bertujuan untuk merumuskan teknik dan juga mencari jawaban terhadap perspektif pelaku. Fokus dari penelitian ini adalah untuk mengungkapkan masalah yang terkait dengan teknik tuning, merujuk pada musik gamelan yang ada, dan menentukan rentang, serta gamelan gamelan. Mulai dari sudut pandang ini, penelitian ini akan menggunakan metode kualitatif untuk mengumpulkan dan mengolah data dari aktor, pemilik gamelan, dan seniman sebagai pengguna. Laras gamelan Jawa. ABSTRACTJavanese gamelan tunings research is an attempt to formulate a Javanese gamelan tunings techniques. There are various issues that still a mystery in Pelaras gamelan. There has been no theory or the workings of gamelan tunings, pelaras generally still rely on instinct and experience. This resulted in the next generation is difficult to imitate the senior generation, and it is possible gamelan tunings science is distorted due to the death of Umpu pelaras gamelan. This study aims to formulate techniques and also seek answers gamelan tunings issues from the perspective of the perpetrator (pelaras gamelan). The focus of this study is to reveal the problems associated with the technique tunings, mbabon process (refer to the existing gamelan tones), and specify ranges, as well as embat gamelan. Starting from this point of view, the study will use a method kulalitatif to collect and process data from pelaras (actor), the owner of gamelan, and artists as a user. Through this way is expected to uncover problems Javanese gamelan tunings.